PATTERNS AND TRENDS OF SOCIO-ECONOMIC DEVELOPMENT OF OMSK REGION: THE SPATIAL ASPECT - M. A. Miller (Вестник СибАДИ, 2018)
Introduction. The article is devoted to the study of socio-economic development of Omsk region from the point of view of spatial organization.  The purpose of this article is to clarify the patterns and trends of spatial  socio-economic development of Omsk region, concerning the nature of their  display in the last decade of this century and taking into account the spatial aspect.Materials and methods. For realization of the research such methods as description, generalization, comparison, and the method of analysis of statistical materials were used.Results. The main results of the research are the specification of patterns defining the spatial development of the Omsk region and associating with the settling of the population, and important industrial and agricultural component of the region economic system. In addition, six trends of socioeconomic development of the Omsk region were identified and studied. The article develops gained and described in the scientific literature,  theoretical and methodological concepts, related to spatial economy and  spatial organisation at the macro – and meso-levels. The article provides the  author’s definition of spatial socio-economic development of the region,  which refers to such an organization of population, infrastructure and  industrial components, which provides them with balanced costs and demand combination with the simultaneous preservation of the territorial unity.Conclusion. The conducted research and the obtained results allow to supplement spatial-economic research area with the approach. identifying  and summarizing patterns and trends of socio-economic development of a particular region, and take into account the s